787 Ablation of the ventricular ectopic foci: a therapeutic option for dilated cardiomyopathy due to arrhythmic MVP. (8th December 2021) - Pistelli, Lorenzo; Giustetto, Carla; Anselmino, Matteo; De Lio, Francesca; Ferraris, Federico; Landi, Irene; Frea, Simone; Faletti, Riccardo; Gatti, Marco; Gaita, Fiorenzo; De Ferrari, Gaetano Maria
Abstract: Aims: A subset of patients with mitral valve prolapse (MVP) are affected by a still not well understood condition characterized by frequent ventricular arrhythmias (mostly originating from papillary muscles) and sudden cardiac death (SCD). It is called MVP malignant syndrome (MVP MS). In these patients, the high arrhythmic burden may lead to left ventricular (LV) dyssynchrony and dysfunction, determining a tachycardia-induced cardiomyopathy (TIC). Reduction in arrhythmic burden determines LV recovery and ejection fraction improvement and interrupts LV progressive dilatation. Methods and reports: We report the case of a 52-year-old woman with MVP and family history of both MVP and SCD who was referred to our department for symptomatic extrasystoles and dyspnoea during exercise. Palpitations begun 11 years before: in that occasion she performed a 3-lead-ECG-Holter monitoring which documented 3457 ventricular extrasystoles. Transthoracic echocardiography (TTE) showed normal LV dimension and function and a myxomatous mitral valve with prolapse of both leaflets. At that time beta-blocker therapy was introduced, but soon suspended because of patient's clinical intolerance (bradycardia and hypotension). Since then she was lost at follow-up for years, until symptoms worsened. When she came to our attention, TTE showed dilated and hypokinetic LV (ejection fraction was 38%, S2 wave at TDI was 6.4 cm/s and global longitudinal strain value was −13%). CMR was performed and confirmed TTE findings. Mitral-annulus disjunction was described in anterior, lateral, and posterior wall and late gadolinium enhancement analyses showed subendocardial fibrosis in correspondence of the posterior papillary muscle (PM) and in the mid-inferior wall. Holter monitoring enlightened a high arrhythmic burden with 24 065 premature ventricular complexes (PVCs) of two morphologies (right bundle branch block-like and −120° axis and right bundle branch block-like and −75° axis). During stress test, PVCs increased as the heart rate increased, resulting in bigeminism at peak exercise. Considering all these features, we hypothesized a case of MVP MS in which the high ventricular arrhythmic burden resulted in TIC. Any available pharmacological attempt to reduce arrhythmias failed. Transcatheter (TC) ablation of PVCs was then proposed. Electrophysiological study identified the inner part of the posterior papillary muscle implantation region and the antero-lateral basal wall as PVCs sites of origin. Radiofrequency ablation was performed in both sites. After the procedure, despite an incomplete suppression of the posterior PM focus, 12-lead 24-h Holter monitoring and TTE performed during the hospitalization showed a consistent arrhythmic burden reduction and LV function improvement. At 6 months from the procedure, symptoms improved and Holter monitoring showed 7515 PVCs with a 54% arrhythmic burden reduction compared with the presentation. TE showed lower LV end-diastolic volume and an increase in ejection fraction up to 47%; global longitudinal strain was −17% and TDI showed a S2 wave on lateral wall of 11 cm/s, confirming left ventricle improvement after the arrhythmic burden reduction. Conclusions: Complete suppression of PMs PVCs with TC ablation is difficult to obtain, especially when the focus is in the inner part of the PM and TC ablation of ventricular arrhythmias in MVP patients has not yet demonstrated his efficacy in reducing SCD. Nevertheless, it should be taken into consideration to obtain at least PVCs reduction in patients with high arrhythmic burden leading to TIC.